Bonfire of kashmiriyat : deconstructing the accession - Bamzai; Sandeep ([S.l.] : Rupa, 2007)
Scholarly study of partition, Kashmir nationalism, conflict over communalism, Chamber of Princes, accession to India. Major contribution to partition literature,history of modern India.
Keywords: India--Jammu and Kashmir; Political science